Comparison of cognitive strength and weaknesses between visually impaired children and non-visually impaired children - Dewanti, Novellia Ardhya; Mayantya, Dhasthra Laksita; Ardiana, Brigita Yuriza; Wicaksono, Banyu (Psychological Research and Intervention, 2022)
Visually impaired children experience limitation in learning and identifying the world.  There has yet to be an intelligence measuring instrument tailor made to accommodate their limitations. Therefore, this study aims explore strengths and weaknesses of visually impaired children compared to non-visually impaired children in standard intelligence test as a pilot study for constructing intelligence test that is tailor made for visually impaired children.  This research is a quantitative approach using WISC-R as the research instrumenrs. The data was analyzed using Mann-Whitney U Test. This study found a significant difficulty experienced by visually impaired children in performance subtest. Further, no significant difference in verbal IQ was found between visually impaired children and non-visually impaired children. The results of this study are expected to be the basis for developing intelligence measuring tools for visually impaired children in the future.